2008
DOI: 10.1088/0953-8984/20/6/064206
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of a solid/liquid interface: a combined force field and first principles approach to the structure and dynamics of acetonitrile near an anatase surface

Abstract: Atomistic simulations of a solid/liquid interface: a combined force field and first principles approach to the structure and dynamics of acetonitrile near an anatase surface Schiffmann, F; Hutter, J; VandeVondele, J Schiffmann, F;Hutter, J; VandeVondele, J (2008). Atomistic simulations of a solid/liquid interface: a combined force field and first principles approach to the structure and dynamics of acetonitrile near an anatase surface. Atomistic simulations of a solid/liquid interface: a combined force field a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 46 publications
(90 reference statements)
7
48
1
Order By: Relevance
“…The observed structure can therefore not be attributed to a correlation between ions, but must be induced by the solvent. In previous work, we have observed a strong layering of the acetonitrile near the anatase(101) surface, due to a favorable interaction of the nitrile group with the titanium atoms of the surface, and the pronounced dipolar nature of the solvent (14). Here, we observe that the structure of the liquid, as illustrated with a density profile in Fig.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The observed structure can therefore not be attributed to a correlation between ions, but must be induced by the solvent. In previous work, we have observed a strong layering of the acetonitrile near the anatase(101) surface, due to a favorable interaction of the nitrile group with the titanium atoms of the surface, and the pronounced dipolar nature of the solvent (14). Here, we observe that the structure of the liquid, as illustrated with a density profile in Fig.…”
supporting
confidence: 66%
“…The plane wave density cutoff was set to 280 Ry. The FF for acetonitrile is based on point charges, van der Waals interactions and harmonic bonded terms as found in literature (21), TiO 2 was modeled using point charges, and a Buckingham potential from literature (22), while the interaction between both species has been derived and validated against ab initio data in our earlier work (14). Parameters for the cations have been taken from literature (23,24), for fluoride we employed σ ¼ 2.90 Å and ϵ ¼ 0.105 kJ∕mol, for chloride σ ¼ 4.04 Å and ϵ ¼ 0.157 kJ∕mol, for iodide σ ¼ 4.60 Å and ϵ ¼ 0.438 kJ∕mol similar to ref.…”
Section: Methodsmentioning
confidence: 99%
“…The authors also carried out in situ vibrational spectroscopy and could thus confirm the reversible binding of I 2 to the thiocyanate group. Furthermore, Schiffmann et al were able to simulate the electrolyte near the interface and found that acetonitrile is able to cover the (101) surface of anatase with a passivating layer that inhibits direct contact of the redox mediator with the oxide [229,230]. It was also observed that the solvent structure specifically enhances the concentration of I À at a distance which further favors rapid dye regeneration.…”
Section: Complex Electrochemical Interfaces and Electrochemical Reactmentioning
confidence: 99%
“…However statistically relevant calculations based on MD are computationally prohibitive 4 and force fields cannot, to this date, provide a satisfactory atomistic description of the interactions between mixed phase systems. 20 Density Functional Theory (DFT) calculations of the charge donor/acceptor coupled with a continuum model for the surroundings is an attractive alternative. Small inhomogeneities in the medium can be accounted for using dielectric mixing theory 21 and recent development of the Polarizable Continuum Model (PCM) allows anisotropic media to be implemented (i.e.…”
Section: Introductionmentioning
confidence: 99%